Social toothbrush: fostering family nudging around tooth brushing habits - Caraban, Ana; Ferreira, Maria José; Gouveia, Rúben; Karapanos, Evangelos (My University, 2015)
The earlier in life an individual adopts healthy practices the more impact those practices have on the long term. In this paper we present Social Toothbrush, a hardware plugin for electric toothbrushes that aims to induce proper tooth brushing behaviors on young children and adults. Social Toothbrush does so by taking advantage of family communication and coordination practices to encourage healthy practices. We first describe the theoretical grounding of our design process, Social Translucence, followed by the design and development of Social Toothbrush.
Keywords: Behavior change; Family; Persuasive technology; Tooth brushing; Ubiquitous computing